2005
DOI: 10.1016/j.ympev.2004.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ITS sequence data for phylogenetic reconstruction of Italian Quercus spp.

Abstract: Nuclear ribosomal DNA sequences encoding the 5.8S RNA and the Xanking internal transcribed spacers (ITS1 and ITS2) were used to test the phylogenetic relationships within 12 Italian Quercus taxa (Fagaceae). Hypotheses of sequence orthology are tested by detailed inspection of some basic features of oak ITS sequences (i.e., general patterns of conserved domains, thermodynamic stability and predicted conformation of the secondary structure of transcripts) that also allowed more accurate sequence alignment. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 65 publications
5
62
1
Order By: Relevance
“…The wind-pollinated genus Quercus has been wellstudied using molecular phylogenetics and two major clades have been identified (Manos et al 1999;Bellarosa et al 2005;Oh and Manos 2008;Denk and Grimm 2010). The larger of the two clades has been referred to as the New World oaks with sections Lobatae (red and black oaks), Protobalanus (golden cup oaks), and Quercus s.s. (white oaks).…”
Section: Taxonomy and Phylogenymentioning
confidence: 99%
“…The wind-pollinated genus Quercus has been wellstudied using molecular phylogenetics and two major clades have been identified (Manos et al 1999;Bellarosa et al 2005;Oh and Manos 2008;Denk and Grimm 2010). The larger of the two clades has been referred to as the New World oaks with sections Lobatae (red and black oaks), Protobalanus (golden cup oaks), and Quercus s.s. (white oaks).…”
Section: Taxonomy and Phylogenymentioning
confidence: 99%
“…sequences available in GenBank. Universal ITS primers and PCR conditions followed Bellarosa et al (2005). PCR products were cleaned with Illustra DNA and Gel Band Purification Kit (GE Healthcare), and eluted in 30 μl type 6 elution buffer.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Putative hybrids with parental morphology (Toumi and Lumaret, 1998;Belahbib et al, 2001;Staudt et al, 2004), intermediate morphology (Toumi and Lumaret, 1998;Lumaret et al, 2002;Bellarosa et al, 2005) or leaf morphology skewed toward Q. ilex (Staudt et al, 2004) have been reported. Bark cannot be used as a discriminating feature because F1s are considered to lack cork and, thus, they could be confused with pure Q. ilex (Lumaret et al, 2002;Bellarosa et al, 2005). The existence of morphologically cryptic hybrids seems to be the only certainty.…”
Section: Hybrid Identitymentioning
confidence: 99%
“…Within the section Cerris (subgenus Quercus), Q. suber and Q. ilex belong to different clades (groups Cerris and Ilex, respectively), which are thought to have diverged during the middle Tertiary (Manos et al, 2001). Despite their deep phylogenetic divergence, clearly supported by internal transcribed spacer, amplified fragment length polymorphisms and isozyme variation (Manos et al, 1999;Toumi and Lumaret, 2001;Bellarosa et al, 2005;Ló pez de Heredia et al, 2007b), hybridization has been inferred on the basis of morphological and molecular markers (Elena-Rosselló et al, 1992;Toumi and Lumaret, 1998;Lumaret et al, 2002;Oliveira et al, 2003;Bellarosa et al, 2005). Furthermore, extensive surveys of chloroplast DNA diversity of both species and of other relatives (such as Q. coccifera) across the whole distribution range have demonstrated widespread cytoplasmic introgression, mainly localized along a northeast-southwest line, from French Catalonia and eastern Iberia to Morocco (reviewed in Lumaret et al, 2005).…”
Section: Introductionmentioning
confidence: 99%